The Effect of Competence and Work Discipline on Work Productivity of Employee - Annisa Fitriasari; Puspita Wulansari (Almana : Jurnal Manajemen dan Bisnis, 2020)
To achieve organizational goals, quality human resources are needed to produce high productivity. This research serves the purpose of knowing the level of competency, work discipline, and employees’ productivity as well as the effect of competency and work discipline, whether partially or simultaneously, towards the employees’ productivity in Dinas Kependudukan dan Pencatatan Sipil Kota Bandung. The method applied in this research is a quantitative method with the purpose of descriptive research. The researcher prepared a questioner that later shared with as many as 105 respondents. This research makes use of validity and reliability tests. The analysis methods used in this research are descriptive analysis, the classical assumption test, and multiple linear regression. Based on the result of data processed in Disdukcapil Kota Bandung, employees value competency as much as 82.54%, work discipline 81.17%, and employees’ productivity 85.32%. This means competency and productivity place in the highest category, meanwhile, work discipline in the high category. The result of the research shows that, partially and simultaneously, competency and work discipline has a significant effect on employees’ productivity for Dinas Kependudukan dan Pencatatan Sipil Kota Bandung.